Risk Factors for Cerebral Palsy in Brazilian Children: A Case-Control Study (Research, Society and Development, 2021)
Background: Cerebral palsy is the main cause of physical disability in childhood. Objectives: This study analyzed prenatal and perinatal risk factors that contribute to cerebral palsy in Brazilian children. Methods: A case-control study was conducted with 2- to 10-year-old children in the city of Aracaju, Sergipe, Brazil. The cases were population-based, selected from the Primary Health Care services. The controls were selected from the database of the Brazilian Live Births Information System. Controls were paired with cases by gender, year, and hospital of birth. Results: A total of 570 participants (114 cases and 456 controls) were studied. Most of the participants were male, with bilateral spastic cerebral palsy. Among the prenatal factors examined, the presence of congenital anomalies was significantly different between cases and controls (OR = 54.28, [95% CI 12.55, 234.86]). The analysis of perinatal factors revealed significant differences between cases and controls in low birth weight (OR = 3.8, [95% CI 2.34, 6.16]), preterm birth (OR = 2.31, [95% CI 1.41, 3.80]), and low Apgar scores (OR = 14.73, [95% CI 5.27, 41.15]). Conclusions: The main prenatal and perinatal factors associated with cerebral palsy in our population were congenital anomalies, low Apgar scores, low birth weight, and preterm birth. The perinatal period had more risk factors, demanding a deeper study of their causes and of possible preventive measures.